Arson or fire setting in offenders with intellectual disability: Clinical characteristics, forensic histories, and treatment outcomes. Issue Volume 40:Issue2(2015) (3rd April 2015) - Alexander, Regi T.; Chester, Verity; Green, Fatima N.; Gunaratna, Ignatius; Hoare, Sudeep
Abstract: Background Although many with intellectual disability come to the attention of services for fire setting, research in this area is scarce, which poses challenges for management. Method In this paper we examined those with a fire-setting history ( n  = 30), identified from a sample of 138 patients treated in a UK forensic intellectual disability service. Those with a fire-setting history were compared to those without this history on various clinical, forensic, and treatment outcome variables. Results Fire-setting was associated with significant psychopathology, including psychosis and personality disorders. Only half of the fire setters had a formal arson conviction. Fire setters were more likely to have a violence conviction and criminal sections/restriction orders. Conclusions Half of those with fire-setting histories did not have formal arson convictions, highlighting the need for thorough history taking. Prevalent comorbidity suggests interventions should focus on treating psychopathology before commencing offence-specific arson therapies.